The Effect of Social Media Marketing, Influencer Marketing, and Consumer Engagement on Purchase Intention in Local Cosmetic Products - shandy lim; Erilia Kesumahati (Enrichment : Journal of Management, 2022)
This study aims to analyze the impact of social media marketing, influencer marketing, and consumer engagement on purchase intention in local cosmetic products. This study used quantitative methods and data collected by questionnaire technique. The respondent's study included as many as 226 people living in Batam City on the condition that they purchased local cosmetic products. Four hypotheses were formulated and tested using t-test analysis. The results showed that influencer marketing and consumer engagement significantly positively affected purchase intention. Meanwhile, the impact of social media marketing on purchase intentions was insignificant.